Adding an invasive procedure will not necessarily change treatment or outcome of NSCLC patients with preoperative clinical N1 disease. Issue 4 (5th April 2018) - Addeo, Alfredo; Banna, Giuseppe
We have read with great interest and welcome the publication of a prospective multicentre study regarding the role of mediastinal staging by video-assisted mediastinoscopy (VAM) in patients with clinical N1 (cN1) nonsmall cell lung cancer (NSCLC) [1]. The objective of the study was to assess the sensitivity, negative predictive value and accuracy of VAM in a well-defined group of patients with cN1. Video-assisted mediastinoscopy or VAM-lymphadenectomy is not a standard procedure in cN1 disease http://ow.ly/dAZq30irs63